Development of Technology for Processing Pyrite Cinder to Produce Non-Ferrous Metal Concentrate - Abikak, Yerkezhan Baimuratovna; Kenzhaliev, Bagdaulet Kenzhalievich; Gladyshev, Sergei Vladilenovich; Abdulvaliev, Rinat Anvarbekovich (Universitas Negeri Padang, 2022)
The existing technologies for processing of pyrite cinder require improvement for complex extraction of non-ferrous, precious metals and iron. The novelty of the technology used in the work for the processing of pyrite cinders is the preliminary chemical activation in a solution of sodium bicarbonate. The optimal activation modes were determined according to temperature, duration, L:S ratio and NaHCO3 concentration. It has been established that activation of pyrite cinder results in changes in phase composition and a reduction in the content of the impurity components P2O5, SO3 and As2O3. The leaching of pyrite cinder after pre-activation in 15 % H2SO4 solution resulted in an extraction into solution, wt. %: CuO 76, 8; ZnO 75, 9 and Fe2O3 26, 0. The degree of extraction of non-ferrous metals in sulphuric acid solution without chemical activation is lower by 15 - 20 %.